The Concept of Low‑Value in the Context of Fixed Assets - Hołda, Artur; Staszel, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
This article aims to present the possibilities of making simplifications to accounting, particularly in the recognition of fixed assets and other carrying value items, according to the principle of relevance and fair presentation. In order to achieve this aim, the authors used deductive and inductive research methods, such as a literature review, analyses of the content of financial statements, and statistical verifications of the findings. Simplifications may be made to accounting provided that this does not distort a given entity’s true financial picture, and thereby does not mislead the users of the financial statement; making it irrelevant. Establishing the levels at which some type of information should be deemed relevant is difficult but crucial in reporting and financial audit. The authors of the article propose a model to enable establishing the levels of relevance (with regard to both the financial statement as a whole and its components) in each economic entity, regardless of its size and industry in which it operates. This model was created based on the reporting data of Polish companies, constituting a correction of similar models applied in Western Europe. It facilitates the definition of an objectified level of partial relevance basically for all reporting items. The authors used this model to research 148 companies by analysing their financial reports of 2007–2014, thereby reviewing the data of 1,184 financial statements, and other 337 smaller entities by analysing their financial reports of 2010–2017, thereby reviewing the data of 2,696 financial statements. In total, the authors analysed data from 3,880 financial statements. As a result, they drew conclusions as to the possibility of making simplifications in the recognition of fixed assets by entities. This research made it possible to establish the levels of relevance for the entities listed on WIG30, mWIG40, and sWIG80 as well as for the stock exchange companies not listed on any of the indices named, par ticularly the partial relevance considered for depreciation (amortisation). The analysis of the research results, including the application of the Chi square test, has led to the question whether from the financial accounting point of view making one‑off depreciations in the amounts of approx. PLN 10,000 (which the entities may want to practice in relation to the amendment to tax regulations) does not distort a given entity’s financial picture in the view of its financial statement. The research hypothesis of the study assumes that not all entities maintaining accounting books may apply tax regulations in the field of recognition of low‑value fixed assets. The analysis of the data contained in 3,880 financial statements of both larger and smaller entities has shown that the following research hypothesis should be adopted: not all entities maintaining accounting records may apply tax regulations for the recognition of low‑value fixed assets.